Study of P-350 cement setting kinetic by nuclear magnetic resonance - Duque Fernández, Gabriel L.; Díaz Quintanilla, David; Capote Rodríguez, Rogelio; Zapata Sierra, Manuel (Materiales de Construcción, 1993)
A kinetic study of cement setting process is presented in this paper A new method which allows the microscopic research of the evolution of the cement hydration applied to the study of three P-350 cuban cements is used. The initial and final values of the specific surfaces of the hydration products and cement were obtained, and the different periods of the hydration process of cement pastes were characterized. The influence of the cement phase composition on the surface development of the hydrated cement stone is discussed.